OP80 Impact Of Patient Group Participation At Scottish Medicines Consortium Committee Meetings. (2019) - Dickson, Jennifer; Lockhart, Lindsay; Taylor, Louise; McCormack, Jackie; Walker, Laura
Abstract : Introduction: The Scottish Medicines Consortium (SMC) encourages patient group (PG) representatives to participate in the decision-making committee meetings, answering questions from committee members and providing points of clarity throughout discussions if required. In a continuous improvement approach the process and the participant experience is continually evaluated to monitor impact and emerging themes. Methods: The interactions between committee members and PG representatives are recorded in writing by the public involvement team to monitor the questions or points of clarity raised. These interactions were analyzed using thematic analysis to look for emerging themes. Following the meeting, PG representatives are invited to complete an online survey on their experience of working with SMC. Results: From July 2017 to October 2018, 36 PG representatives have attended committee meetings for the discussion of their submission. Committee members asked 17 PG representatives to contribute. Key themes that have emerged to date include insight into the impact of living with the condition on quality of life and how a new medicine may affect this. Survey feedback has been positive with participants reporting that patient engagement has been strengthened, and that the patient voice is heard, valued and supports committee members in making fully informed decisions. PG representatives expressed a willingness to participate again. Feedback also highlighted that the preparatory support offered to PG representatives by the public involvement team is highly valued. Conclusions: Patient group participation in committee meetings has been received positively by PG representatives. They report that discussions relating to quality of life impact of medicines on patients and carers better reflect the lived experience, enriching committee's deliberations. This demonstrates SMCs commitment to openness and transparency and has strengthened patient engagement in our processes.